1998
DOI: 10.1248/bpb.21.1306
|View full text |Cite
|
Sign up to set email alerts
|

The Promoting Effects of Geniposidic Acid and Aucubin in Eucommia ulmoides OLIVER Leaves on Collagen Synthesis.

Abstract: We have reported that collagen synthesis was stimulated by the administration of a hot water extract from the leaves of Eucommia ulmoides OLIVER, Eucommiaceae (Du-Zhong leaves) in false aged model rats. In this paper, we set out to examine the compounds in Du-Zhong leaves that stimulated collagen synthesis in false aged model rats. In experiment 1, a methanol extract of Du-Zhong leaves also stimulated collagen synthesis in aged model rats. An acetone fraction was derived from the methanol extract by silica gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Our previous study also indicated that the compound of calcium phosphate cement and EuO extracts promoted proliferation and adhesion of MC3T3-E1 osteoblasts in vitro (Lin et al, 2008). The pharmacological effects of EuO leaves on bone and muscle are closely related to collagen metabolism (Li et al, 1998). Granuloma formation and collagen synthesis were significantly increased by the administration of methanol extracts of EuO cortex (Li et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study also indicated that the compound of calcium phosphate cement and EuO extracts promoted proliferation and adhesion of MC3T3-E1 osteoblasts in vitro (Lin et al, 2008). The pharmacological effects of EuO leaves on bone and muscle are closely related to collagen metabolism (Li et al, 1998). Granuloma formation and collagen synthesis were significantly increased by the administration of methanol extracts of EuO cortex (Li et al, 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (1998) reported that collagen synthesis in the aged-rat model was stimulated by the administration of hot water-extracts from EuO leaves. Ha et al (2003) reported that EuO influences osteoblastic differentiation and prevents bone loss, and concluded that an EuO fraction with high polarity might contain active constituents stimulating the proliferation of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Aucubin, a natural compound has been found in various plants including leaves of Aucuba japonica [15] and Eucommia ulmoides [16], proves to possess a variety of pharmacological effects [17][18][19]; [20], notably, anti-inflammatory effect [21]. It has been reported to have blocked the translocation of NF-κB by inhibition of IκB degradation and phosphorylation, a critical step in early inflammatory responses [22].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…1b). GPA promotes collagen synthesis [11], and GPS has anti-inflammatory activity [12], activity against the *Corresponding author. E-mail: xqchen@mail.csu.edu.cn tumor-promoting compound 12-O-tetradecanoyl-phorbol-13-acetate [13][14], and is a treatment for liver disorder [15].…”
Section: Introductionmentioning
confidence: 99%